2019
DOI: 10.31372/20190402.1028
|View full text |Cite
|
Sign up to set email alerts
|

Family Support towards Resilience in Adolescents with Type I Diabetes: A Preliminary Study in Indonesia

Abstract: The prevalence of diabetes has increased in adolescents. Diabetic adolescents need ongoing support from their families, and the family plays an important role in the management of the disorder. This study aimed to identify the relationship between family support and resilience in adolescents with Type 1 Diabetes Mellitus (T1DM). Quantitative data analysis was conducted using simple logistic regression. Meanwhile, qualitative data were analyzed using content analysis. The results show that the median duration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Therefore, it is important to know and support the strengths and protective factors that increase resilience in patients with T1DM ( 14 , 18 ). In the literature, collaborative parental involvement, supportive family communication, problem-solving skills, and diabetes self-efficacy have been identified as strengths that contribute to resilience in the face of diabetes-related challenges ( 18 , 19 , 20 ). Despite the known advantages of resilience, the assessment and promotion of resilience often takes a back seat to the evaluation of problems and obstacles related to diabetes management in pediatric research and practice ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to know and support the strengths and protective factors that increase resilience in patients with T1DM ( 14 , 18 ). In the literature, collaborative parental involvement, supportive family communication, problem-solving skills, and diabetes self-efficacy have been identified as strengths that contribute to resilience in the face of diabetes-related challenges ( 18 , 19 , 20 ). Despite the known advantages of resilience, the assessment and promotion of resilience often takes a back seat to the evaluation of problems and obstacles related to diabetes management in pediatric research and practice ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the results of the linear regression, the final model indicates that Intrafamilial Relationships, Connectedness with school, and with peers maintained a predictive power of 29% derived from a positive family dynamic tend to promote higher levels of resilience and lower negative results derived from exposure to adverse events (Agustini et al, 2019;Oldfield et al, 2016;Ross et al, 2017). As mentioned by Dias and Cadime (2017), the family environment shapes how the adolescent understands adversity, providing a key context for developing effective coping skills and obtaining the necessary support to face adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this investigation was to analyze the predictive value of intrafamilial relationships, connectedness with school and peers over Resilience in Mexican adolescents. An important contribution of this study was to explore the interaction between these variables in a general adolescent population, considering that previous research has analyzed this relationship in depth with individuals who face specific difficulties (Acuña & Kataoka, 2017;Agustini et al, 2019;Villalobos-Parada et al, 2016;Yablón, 2019). In the results, we found that the quality of the connection that is perceived with these environments also maintains a significant influence over the resilience of adolescents in the general population, identifying that family is one of the systems with greatest influence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…People also will experience tranquility and a lack of load from their illness or troubles. Another crucial factor is how family support can make people more resilient and open-minded in the face of adversity (Agustini et al, 2019). The individual's medication process involves the family's role significantly.…”
Section: The Effect Of Family Support On Quality Of Lifementioning
confidence: 99%